A Genocide that Precedes Genocide: Reconciling "genocide" and "indigeneity" with a paradox of otherness. (June 2016) - Chalmers, Jason
Genocide and settler colonialism are conceptually related ideas, although the specific relationship remains unclear. Whereas some scholars develop subcategories of "colonial genocide" or examine the historical origins of these concepts, I address the signification of "genocide" and "indigeneity." I explore the system of meanings underlying each concept to suggest that both are paradoxically rooted in otherness. The category of indigeneity reveals a basic paradox: the colonizer and Indigenous other are separate from but, simultaneously, dependent upon one another. Likewise, with genocide the perpetrator and othered victim are separate but at the same time dependent on each other. Genocide and indigeneity are conceptually related so that one can consider them as two aspects of the same phenomenon. I propose conceptualizing the relationship between indigeneity and genocide as a two-stage process of erasure in settler societies, with imposition of the category of indigeneity as a preliminary genocide that precedes a formal act of genocide.